Critical Ethnic Studies : A Reader - Hernández, David, 1967-; See, Sarita Echavez; Rodriguez, Dylan; Redmond, Shana L.; Kim, Jodi, 1970-; Elia, Nada (Book collections on Project MUSE., 2016)
Building on the possibilities opened up by Ethnic Studies, this volume promotes open dialogue, discussion, and debate regarding Critical Ethnic Studies' expansive, politically complex, and intellectually rich concerns on topics ranging from multiculturalism and the neoliberal university to the militarized security state.